The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/02786820290038500
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of Aerosol Spectrometers for Ambient Air Monitoring

Abstract: Three aerosol spectrometers measuring the number concentration distribution of particles in the diameter range 0.01 to 2.5 ¹m were compared by running them side-by-side for 385 h under ambient air conditions in Erfurt, Germany in October 1997. From the spectral data the measured hourly number concentrations in 3 size fractions, the ultra ne fraction (0.01-0.1 ¹m), the accumulation fraction (0.1-0.5 ¹m), and the coarse fraction (0.5-2.5 ¹m), were analyzed. The systematic component of the difference between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The accuracy of particle concentration measurements for PM 2.5 is within 20% as was estimated by comparing these instruments with other aerosol counters and spectrometers (Khlystov et al, 2001;Mirme et al, 2002). Hinds and Kraske (1986) showed that the LAS-X sampling efficiency decreases for this fraction: about 30% loss of 10 mm particles at the sampling rate of 5 cm 3 s À1 .…”
Section: Experimental Set-upmentioning
confidence: 91%
“…The accuracy of particle concentration measurements for PM 2.5 is within 20% as was estimated by comparing these instruments with other aerosol counters and spectrometers (Khlystov et al, 2001;Mirme et al, 2002). Hinds and Kraske (1986) showed that the LAS-X sampling efficiency decreases for this fraction: about 30% loss of 10 mm particles at the sampling rate of 5 cm 3 s À1 .…”
Section: Experimental Set-upmentioning
confidence: 91%
“…As the aerosol spectrometers were based on di!erent measurement principles and there is no standard instrument available for making comparative measurements of the particle fractions of interest, side by side comparison of the three spectrometers was performed prior to the "eld measurement campaign Mirme et al, 2000). The side by side comparison tests were also made in a laboratory with three di!erent kinds of arti"cial test aerosols .…”
Section: Quality Assurance and Controlmentioning
confidence: 99%
“…In each city, concentrations of ambient air pollutants were measured at a fixed monitoring site representing urban background levels according to the ULTRA SOPs (Pekkanen and Timonen 2000). Size distributions of particle number concentrations were measured with aerosol spectrometers, which had been compared thoroughly in previous side-by-side ambient air measurements Mirme et al 2002;Tuch et al 2000). Fractions of number concentrations in different size classes were determined to form one size class for UFP, (particles in the size range of 0.01-0.1 µm) and one for accumulation mode particles (ACP), (particles in the size range of 0.1-1.0 µm existing networks.…”
mentioning
confidence: 99%